2006
DOI: 10.1021/jp062985y
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study of Small Neutral and Charged Silver Cluster Hydrides

Abstract: Small neutral, anionic, and cationic silver cluster hydrides AgnH and anionic HAgnH (n=1-7) have been studied using the PW91PW91 density functional method. It was found that the most stable structure of the AgnH complex (neutral or charged) does not always come from that of the lowest energy bare silver cluster plus an attached H atom. Among various possible adsorption sites, the bridge site is energetically preferred for the cationic and most cases of neutral Agn. For anionic Agn, the top site is preferred fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 25 publications
5
29
0
Order By: Relevance
“…4, there are two stable structures for Ag 2 H − and Ag 2 H, respectively. The C 2v triangular structure of Ag 2 H predicted in earlier theoretical studies 21,22 turned out to have imaginary frequencies in our calculations. For Ag 2 H − , the lowest energy structure in our results has C ∞ν geometry.…”
Section: B Ag 2 H − and Ag 2 Hsupporting
confidence: 59%
See 1 more Smart Citation
“…4, there are two stable structures for Ag 2 H − and Ag 2 H, respectively. The C 2v triangular structure of Ag 2 H predicted in earlier theoretical studies 21,22 turned out to have imaginary frequencies in our calculations. For Ag 2 H − , the lowest energy structure in our results has C ∞ν geometry.…”
Section: B Ag 2 H − and Ag 2 Hsupporting
confidence: 59%
“…Similarly, Khairallah et al 20 found that the structures of Ag n-1 H + (n = 3, 5, and 7) were identical to those of Ag n + based on theoretical studies. Zhao et al 21 extensively studied the neutral and charged Ag n H (n = 1-7) using PW91PW91 density functional method. They found that the bridge sites were the most favorable binding positions for hydrogen atom in all cationic, most of the neutral and the larger anionic clusters, while for Ag n H (n = 3) and Ag n H − (n ≤ 4), the top sites of silver clusters were preferred by hydrogen atom.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] For example, many studies have involved the use of photoelectron spectroscopy (PES) and density functional theory (DFT) calculations to investigate the structure of gold-and silver-containing clusters. [9][10][11][12][13][14][15][16][17][18][19][20] Using these methods, Zhao et al found that Au-H interactions are stronger than Ag-H interactions in metal-hydride species, [18] and Wang and co-workers [17,19] were able to show that relativistic effects [7,21] cause Au to form covalent rather than ionic bonds with certain ligands.…”
mentioning
confidence: 99%
“…Another DFT study was done on small anionic, neutral, and cationic silver cluster hydrides using the PW91PW91 method. Here, binding energies showed different behaviors depending on the number of silver atoms; cationic clusters are the ones with lowest binding energies in clusters with an odd number of silver atoms while neutral clusters are the ones with an even number of silver atoms [11].…”
Section: Introductionmentioning
confidence: 96%